Designing and implementing interactive power factor correction using Visual Basic 6.0 / Shazlina Shamuri - Shamuri, Shazlina (2006)
This paper presents, an interactive power factor correction using capacitor banks application design to reduce time used in calculating the size of corrective capacitor banks. Essentially, power factor is a measurement of how effectively electrical power is being used. The higher the power factor, the more effectively electrical power is being used. Poor power factor happens due to an inductive loads and it can be corrected by reducing the inductive current by applying capacitor banks. Capacitor banks are widely used as it is more practical and economical. Capacitive power factor correction is applied to circuits as a means of reducing inductive load and therefore can be utilised to reduce kVA and electrical costs. In practical, a poor power factor can lead to overloaded generator, transmission lines and transformer greater voltage drop and power losses. This interactive program was created from scratch using VISUAL BASIC software to ease the engineer's burden in calculating the size of capacitor banks required to correct the power factor. Both simulation and experimental results will show the recommended size of capacitor bank required to achieve the required power factor level.